Encapsulation of organic phase change materials within metal oxides for thermal energy storage systems / Sara Tahan Latibari - Sara, Tahan Latibari (2016)

(untitled)
Solar energy is receiving a lot of attention nowadays since it is a clean, renewable, and sustainable energy. A major limitation of solar energy is that it is available for only about 2000 hours a year in many places. Thermal energy storage is a major contributor to bridge the gap between energy demand (consumption) and energy production (supply) by solar power. The utilization of high latent heat storage capability of phase change materials is one of the keys to an efficient way to store thermal energy. Several kinds of organic PCMs like fatty acids have been applied recently as they have a high latent heat and appropriate thermal properties. However, direct use of such PCMs in practical thermal applications is not easy due to their low thermal conductivity, flammability, instability, and leakage problems. To overcome these problems, PCMs have been encapsulated in various organic and inorganic shell materials. An inorganic shell material with high thermal conductivity and superior strength not only enhances the thermal transfer performance of the PCM system but also improves the durability and working reliability of them. This study presents state of the art of nano/microencapsulated PCMs (NE/MEPCMs) for thermal energy storage applications and provides an insight into our efforts to develop novel nano/microencapsulated phase change materials with enhanced performance and safety. Specific attention was given to the encapsulation process of some inorganic materials for the first time and the improvement of thermal conductivity and thermal stability of the prepared materials. In addition, the thermal energy storage properties and performance are discussed for thermal energy applications. In this research three types of nano/microcapsules were prepared with organic fatty acids as the core phase change material and SiO2 (silica), TiO2 (titania), and Al2O3 (aluminum oxide) as the inorganic shell materials through a sol-gel method. The structural, morphological and thermal features of the newly developed NE/MEPCMs iv were evaluated by a series of modern instruments and characterization technologies, including DSC, TGA, FT-IR, TEM, SEM and XRD. The thermal reliability of prepared nano/microcapsules was investigated using a thermal cycler for a large number of heating and cooling processes. In this research the influences of several types of parameters during the preparation method on the morphology, thermal performance and thermal conductivity of the prepared materials have been studied. The experimental results indicate that the fatty acids were successfully encapsulated in the shell materials in spherical shapes. Encapsulated fatty acids confirmed the outstanding phase-change performance with specific heat and thermal stability enhancement. The thermal conductivities of the encapsulated PCMs are significantly improved compared to pure PCMs. In conclusion, the outstanding latent heat, high thermal conductivity, thermal stability and reliability of the prepared nano/microcapsules make these materials appropriate phase change materials for thermal energy storage applications like slurry systems.